Characteristics and outcomes of acute kidney injury in hospitalized COVID-19 patients: A multicenter study by the Turkish society of nephrology - ARIKAN, İZZET HAKKI; TUĞLULAR, ZÜBEYDE SERHAN (PUBLIC LIBRARY SCIENCE, 2021)
Background Acute kidney injury (AKI) is common in coronavirus disease-2019 (COVID-19) and the severity of AKI is linked to adverse outcomes. In this study, we investigated the factors associated with in-hospital outcomes among hospitalized patients with COVID-19 and AKI. Methods In this multicenter retrospective observational study, we evaluated the characteristics and in-hospital renal and patient outcomes of 578 patients with confirmed COVID-19 and AKI. Data were collected from 34 hospitals in Turkey from March 11 to June 30, 2020. AKI definition and staging were based on the Kidney Disease Improving Global Outcomes criteria. Patients with end-stage kidney disease or with a kidney transplant were excluded. Renal outcomes were identified only in discharged patients. Results The median age of the patients was 69 years, and 60.9% were males. The most frequent comorbid conditions were hypertension (70.5%), diabetes mellitus (43.8%), and chronic kidney disease (CKD) (37.6%). The proportions of AKI stages 1, 2, and 3 were 54.0%, 24.7%, and 21.3%, respectively. 291 patients (50.3%) were admitted to the intensive care unit. Renal improvement was complete in 81.7% and partial in 17.2% of the patients who were discharged. Renal outcomes were worse in patients with AKI stage 3 or baseline CKD. The overall in-hospital mortality in patients with AKI was 38.9%. In-hospital mortality rate was not different in patients with preexisting non-dialysis CKD compared to patients without CKD (34.4 versus 34.0%, p = 0.924). By multivariate Cox regression analysis, age (hazard ratio [HR] [95% confidence interval (95%CI)]: 1.01 [1.0-1.03], p = 0.035], male gender (HR [95%CI]: 1.47 [1.04-2.09], p = 0.029), diabetes mellitus (HR [95%CI]: 1.51 [1.06-2.17], p = 0.022) and cerebrovascular disease (HR [95%CI]: 1.82 [1.08-3.07], p = 0.023), serum lactate dehydrogenase (greater than two-fold increase) (HR [95%CI]: 1.55 [1.05-2.30], p = 0.027) and AKI stage 2 (HR [95%CI]: 1.98 [1.25-3.14], p = 0.003) and stage 3 (HR [95%CI]: 2.25 [1.44-3.51], p = 0.0001) were independent predictors of in-hospital mortality. Conclusions Advanced-stage AKI is associated with extremely high mortality among hospitalized COVID-19 patients. Age, male gender, comorbidities, which are risk factors for mortality in patients with COVID-19 in the general population, are also related to in-hospital mortality in patients with AKI. However, preexisting non-dialysis CKD did not increase in-hospital mortality rate among AKI patients. Renal problems continue in a significant portion of the patients who were discharged.
Keywords: CLINICAL CHARACTERISTICS; DIALYSIS PATIENTS; DISEASE; TRANSPLANT; MORTALITY; WUHAN; INFECTION; CKD